Stress, seizures, and epilepsy: Patient narratives - Lang, Johannes D.; Taylor, David C.; Kasper, Burkhard (Epilepsy and Behavior, 2018)
In epilepsy, individual seizures can be triggered by a variety of external and internal stimuli. One of the most common trigger factors reported by patients is stress. However prevalent, stress-related triggering of episodes seems underappreciated in epilepsy for various reasons, and its misinterpretation often leads to other diagnoses, e.g., psychogenic nonepileptic seizures (PNES) or normal reactions. This article illustrates the significant role of stress as a seizure-provoking factor by referring to nine patient narratives. From this perspective, it appears that there are characteristic patterns of stress triggering, e.g., stress-induced sleep disruption, forms of acute stress, or relaxation after stress. Sometimes seizures are mistaken as symptoms of stress. Patient narratives contain interesting clues relating reports about stress and seizure histories to different epilepsy syndromes as well as nonepileptic episodes in a way that can strongly support the diagnostic process. A narrative approach is particularly valuable in this context. Therefore, accounts of stress triggering in seizures and other episodes should not be neglected, but rather taken seriously, sought and actively explored as a crucial element when taking clinical histories in patients with episodic attacks.
EVALuna2:201938